Descripción y relaciones filogenéticas de una nueva especie de Liolaemus (Iguania: Liolaemidae) y notas sobre el grupo de L. montanus de Perú - Gutiérrez, Roberto C. (2018)
A new lizard species of the Liolaemus montanus group endemic of the Andes western slope, Huaytará Province, Huancavelica, Peru is described. This new species of Liolaemus is of medium size (maximum SVL 70.1 mm) and is characterized by presenting a unique color standard in males, where several light-blue scales on the back and side of the body are prominent, and the abdomen is of an intense yellow. Also, the scales of the back and sides of the body are sub-imbricated, with a slight keel and its shape is rounded to triangular. While females, as well as males exhibit pre-cloacal pores. The combination of several states of morphological, morphometric and flake characters and their color standard clearly differentiate these new taxa of the other Liolaemus species, especially of the members of the L. montanus group described for the center and south of Peru. Also, in this study, we present a revision of the taxonomic status and distribution of species of the L. montanus group described or cited for Peru.